2016
DOI: 10.1007/s10646-016-1652-8
|View full text |Cite
|
Sign up to set email alerts
|

Blood lead concentrations in free-ranging Nile crocodiles (Crocodylus niloticus) from South Africa

Abstract: Generally crocodilians have received little attention with regard to the effects of lead toxicity despite their trophic status as apex, generalist predators that utilize both aquatic and terrestrial habitats, thereby exposing them to a potentially wide range of environmental contaminants. During July-October 2010 we collected whole blood from 34 sub-adult and adult free-ranging Nile crocodiles (Crocodylus niloticus) from three separate populations in northeastern South Africa in order to analyze their blood le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Basal concentrations from AF are within the range reported for control animals by Camus et al (1998; Table 3). The highest mean Pb blood of 0.83 µg mL -1 detected in animals from UA is similar to the reported high doses in A. mississippiensis in Louisiana (Camus et al, 1998) and lower than blood Pb concentrations in male C. niloticus from South Africa (Humphries et al, 2022;Warner et al, 2016), where toxic effects were considered likely (Table 3). For birds, Pb levels of intoxication have varied from subclinical (0.5 µg mL -1 ) to severe clinical intoxication (1 µg mL -1 ; Pain et al, 2019) and for mammals, intoxications have occurred from 0.6 to 0.8 µg mL -1 (Ma, 2011).…”
Section: Discussionsupporting
confidence: 78%
“…Basal concentrations from AF are within the range reported for control animals by Camus et al (1998; Table 3). The highest mean Pb blood of 0.83 µg mL -1 detected in animals from UA is similar to the reported high doses in A. mississippiensis in Louisiana (Camus et al, 1998) and lower than blood Pb concentrations in male C. niloticus from South Africa (Humphries et al, 2022;Warner et al, 2016), where toxic effects were considered likely (Table 3). For birds, Pb levels of intoxication have varied from subclinical (0.5 µg mL -1 ) to severe clinical intoxication (1 µg mL -1 ; Pain et al, 2019) and for mammals, intoxications have occurred from 0.6 to 0.8 µg mL -1 (Ma, 2011).…”
Section: Discussionsupporting
confidence: 78%
“…Consequently, trace elements such as Hg and Pb among others, accumulate in crocodilian tissues (Jeffree et al, 2001;Almli et al, 2005;Warner et al, 2016;Quintela et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The literature explains that males, females and juveniles store inorganic elements in different ways (Schneider et al, 2011), but sex has generally been shown to be non-significant in many studies on turtles and crocodilians (Burger et al, 2009;Schneider et al, 2011;Warner et al, 2016). In articles where there is a significant difference in the sex parameter, the authors explain that males may have higher levels than females due to the freeing of small quantities of these elements through eggs by females during nesting and oviposition processes (Delany et al, 1988;Schneider et al, 2011).…”
Section: Biological Dimensionmentioning
confidence: 99%